The Fall and Rise of Free Entreprise: State Intervention in Canadian Shipbuilding, 1945-1966 - Hennessy, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1991)
AbstractWithin the growing literature on Canadian industrial policy, relatively little attention has been paid to the shipbuilding sector. This paper identifies and explores the distinct phases of government intervention in shipbuilding from 1945 to 1965. With the formation of the Canadian Maritime Commission, intervention took many forms, which reflected contradictory, conflicting, and competing interests. Over this period, intervention ranged from aiding reconversion to sustaining marginal yards for national security reasons. Defence considerations would play the largest role throughout this era. In examining the varied interests reflected in the deliberations of the Maritime Commission and the Departments of Defence Production, Finance, and Industry, this study demonstrates thai defence policy cannot be ignored when assessing industrial policy for this era. At least for shipbuilding, government policy appears to have hampered domestic and international competitiveness.